2022
DOI: 10.1039/d2ra00973k
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric fluorescent sensors for nitrite detection in the environment based on carbon dot/Rhodamine B systems

Abstract: A visual ratiometric fluorescent sensor based on blue carbon dot/Rhodamine B is used to selectively detect NO2− in the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 52 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Chemical surface modification introduces various functional groups onto CD surfaces to enhance solubility, reactivity, and specific ligand conjugation [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ] ( Figure 1 a). For instance, Xu et al [ 74 ] reported a ratiometric CD pH sensor enriched with amino groups, enabling them to specifically target lysosomes within living cells.…”
Section: Construction Strategies Of Cds In Detecting Environmental Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical surface modification introduces various functional groups onto CD surfaces to enhance solubility, reactivity, and specific ligand conjugation [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ] ( Figure 1 a). For instance, Xu et al [ 74 ] reported a ratiometric CD pH sensor enriched with amino groups, enabling them to specifically target lysosomes within living cells.…”
Section: Construction Strategies Of Cds In Detecting Environmental Co...mentioning
confidence: 99%
“…Anions: CD-based probes have been employed for detecting various anions, including phosphate (Pi) [ 87 , 103 , 151 ], nitrite (NO 2 − ) [ 68 , 152 ], hypochlorite (ClO − ) [ 153 , 154 ], bisulfite [ 155 ], and sulfide (S 2− ) [ 156 ] in water sources, facilitating the assessment of water quality.…”
Section: Application In Environmental Monitoringmentioning
confidence: 99%
“…32,33 Rhodamine B (RhB) is a common xanthene fluorescent dye, which could be constant as a reference peak of the ratiometric fluorescent probe. 34,35 To the best of our knowledge, there is no relevant report that rhodamine B can directly react with ATP, so it has great potential to act as a reference fluorophore for ATP detection. Furthermore, Cu doping could reduce the FL intensity of CDs effectively and then realize the sensing process from "off" to "on" via the competitive combination of ATP and Cu, giving a possible protocol to design dual-emission CDs.…”
Section: Introductionmentioning
confidence: 99%
“…It could improve the emission characteristics of CDs, enhance the FL, and increase the FL yield . Moreover, compared to the single-emission FL, ratiometric FL could quantitatively detect the analyte through a change in the ratio of the two FL intensities, which eliminates the background signal and environmental interference to a certain extent. , Rhodamine B (RhB) is a common xanthene fluorescent dye, which could be constant as a reference peak of the ratiometric fluorescent probe. , To the best of our knowledge, there is no relevant report that rhodamine B can directly react with ATP, so it has great potential to act as a reference fluorophore for ATP detection. Furthermore, Cu doping could reduce the FL intensity of CDs effectively and then realize the sensing process from “off” to “on” via the competitive combination of ATP and Cu, giving a possible protocol to design dual-emission CDs …”
Section: Introductionmentioning
confidence: 99%